A Survey of DDoS Attack Detection Schemes: Methods, Challenges, and Datasets - Sughanthini, V; Bharathisindhu, P (International Journal of Computer Sciences and Engineering, 2024)
Cloud computing makes use of a significant amount of virtual storage to provide services on demand via the Internet. The main benefits of cloud computing are reduced service costs and the elimination of the need for consumers to set up expensive computer hardware. The rapid integration of cloud computing with business and numerous other domains has prompted scholars to investigate novel, related technologies. Because of the cloud storage server`s scale and accessibility, individual businesses and users bring their apps, data, and facilities to it for computing operations. Despite the advantages, switching from local to remote computing has created several challenges and security issues for service providers as well as clients. The cloud service provider uses several web technologies to supply its services via the Internet, raising fresh security concerns. The DDoS assault, which aims to prevent legitimate users from accessing a target system or network by overloading it with traffic, is the most serious security issue in cloud computing. In light of this, the article covers the principles of cloud computing, as well as its various forms, security concerns, DDoS assaults, and methods for detecting them using performance metrics and datasets. Lastly, a discussion of cloud computing`s difficulties is included.